ENHANCED FUNCTIONAL PERFORMANCE OF WEARABLE ANTENNA IN BODY-AREA NETWORK - Mashhood Kamil; Muhammad Farooq; Bilal Ur Rehman; Kifayat Ullah; Muhammad Kashif Khan; Wasim Habib; Muhammad Amir; Salman Ilahi Siddiqui; Muhammad Iftikhar Khan (Spectrum of Engineering Sciences, 2025)
The interaction between antenna radiation and human tissue has raised critical health questions, as prolonged exposure may contribute to serious health complications, including potentially life-threatening conditions. This study focuses on enhancing antenna performance near the human body by mitigating its biological effects. The primary objective is to minimize the Specific Absorption Rate (SAR), which measures the rate at which the human body absorbs electromagnetic energy. The Electromagnetic Band-Gap (EBG) structures enhance the overall performance and offer the most effective solution due to their low cost, ease of design, and fabrication. Further, this research presents the successful design and simulation of an antenna system that integrates EBG structures to achieve enhanced gain, efficiency, and reduced SAR.